2007
DOI: 10.1007/s00705-007-1072-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumorigenicity of cells carrying recombinant human herpesvirus 8

Abstract: SummaryHuman herpesvirus 8 (HHV-8) infection is associated with the development of Kaposi's sarcoma and primary effusion lymphoma. The cloning of the HHV-8 genome into a bacterial artificial chromosome (BAC) allows researchers to mutate and identify the relative importance of HHV-8 genes essential for growth and replication in tissue culture systems. However, in vivo models to study the impact of such mutations are very limited. Consequently, the objective of this study was to determine whether cells carrying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…We observed that indeed the virus-purged cell population lost their tumorigenic potential upon transplantation in vivo. While establishment of KS-like lesions has also been demonstrated in nude mice with the help of other cell systems [33][34][35][36], this study confirms that tumorigenicity of the rKSHV-HuARLT cell system is virus-dependent. Thus, viral proteins are essential for inducing the tumorigenic phenotype which is reverted when the cells are depleted from the virus, 3D sprouting was shown to be useful to study ex vivo angiogenesis [22] as well as the evasion [37] and KSHV-induced invasion of lymph endothelial cells [10].…”
Section: Discussionsupporting
confidence: 78%
“…We observed that indeed the virus-purged cell population lost their tumorigenic potential upon transplantation in vivo. While establishment of KS-like lesions has also been demonstrated in nude mice with the help of other cell systems [33][34][35][36], this study confirms that tumorigenicity of the rKSHV-HuARLT cell system is virus-dependent. Thus, viral proteins are essential for inducing the tumorigenic phenotype which is reverted when the cells are depleted from the virus, 3D sprouting was shown to be useful to study ex vivo angiogenesis [22] as well as the evasion [37] and KSHV-induced invasion of lymph endothelial cells [10].…”
Section: Discussionsupporting
confidence: 78%
“…The HEK293T cell line is an immortalised line derived from human embryonic kidney, although its phenotype and molecular characteristics are not typical of renal cells [ 44 ]. While it is a non-cancer cell line, HEK293 cells have been demonstrated to grow in immune-compromised mice in vivo to form subcutaneous tumours [ 45 ]. Furthermore, Li et al characterised HEK293T-derived EVs by profiling the protein, mRNA, and miRNA components, and they identified some potentially immunogenic molecules at both RNA and protein levels [ 30 ].…”
Section: Discussionmentioning
confidence: 99%